KONSISTENSI DAN TRANSPARANSI PENGELOLAAN KEUANGAN DALAM RANAH BUDAYA DAN KEARIFAN LOKAL MENYAMA BRAYA - Pancawati, Ni Luh Putu Anom (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2024)
One form of local wisdom possessed by the people of Bali and Lombok is known as menyama braya. Menyama braya is an excellent capital and foundation for creating harmony in life, regardless of ethnic or religious differences as well as race and skin colour, to live together and side by side in society. This research aims to determine the implementation of menyama braya as a form of local culture and wisdom, which is studied through the application of the principle of accountability in the elements of consistency and transparency in the financial management of Banjar Kertha Bhuwana. Using a qualitative research design with descriptive research methods, data collection was carried out using literature and field studies using triangulation techniques. Data analysis techniques are carried out through data collection, data reduction, data presentation and drawing conclusions or verification. The results of the research show that the implementation of consistency and transparency in financial management in the Banjar Kertha Bhuwana organization contains the implementation of the concept of menyama braya, which is included in the implementation of awig-awig as well as decisions taken through the results of the paruman banjar which regulates the obligations and rights of all banjar members. So, in this way, the cultural process and local wisdom values can influence the financial management process in Banjar Kertha Bhuwana to achieve everyday needs and goals